Single‐switch high step‐up boost converter based on a novel voltage multiplier. Issue 14 (11th October 2019) - Zhu, Binxin; Wang, Han; Vilathgamuwa, Don Mahinda
Abstract : A single‐switch high step‐up boost converter based on a novel voltage multiplier (VM) has been proposed in this study. Compared to traditional boost converter, not only the voltage conversion ratio has been increased, but also voltage stress across semiconductor devices has been decreased. Moreover, the voltage conversion ratio and voltage stress of switch of the proposed converter can be adjusted by the number of the VM cells. The control and drive circuits for the proposed converter is as simple as boost converter as there are no additional switches. Working principles and performance characteristics of the proposed converter have been analysed in detail. A 200 W experimental prototype with three VMs has been built to validate the theoretical analysis.